DAMPAK PENGGUNAAN MEDIA SOSIAL TIKTOK DAN WHATSAPPTERHADAP KEDISIPLINAN SISWA DI SDN 04 TANJUNG PUTAT - Dhea Sandari; Yusrain Yusrain; Mauizatul Hasanah (CV. ADIBA AISHA AMIRA, 2024)
This study originated from the discovery of a phenomenon of lack of discipline of class VI B students at SDN 04 Tanjung Putat, one of which is the impact of social media tiktok and whatsapp. The purpose of this study is to describe and find out about: 1) patterns of social media use by students, 2) forms of student discipline, 3) the impact of tiktok and whatsapp social media on student discipline, 4) the role of the class teacher on student discipline. This research uses a qualitative approach and the type of research used is descriptive. The results of the study show that: (1) The pattern of using social media by students a day is at least around seven to eight hours, for social media followers tiktok has around thirty to one hundred while on whatsapp has contacts around thirty to four hundred. On average, social media tiktok and whatsapp are used by students to create content, watch videos, create stories (stories) and to share messages. (2) The forms of student discipline are as follows: a. there are still students doing assignments at school. b. students pay less attention to the teacher's explanation in front of the class because students are bored and sleepy. c. students' lack of responsibility in collecting assignments on time. d. lack of discipline in dressing. e. students are active and diligent in asking questions. (3) The positive impact of social media tiktok and whatsapp is that students are more creative in doing assignments and looking for information as well as active and confident. While the negative impact is the lack of focus on learning and delaying school assignments, as well as exposure to negative content through the behavior shown. (4) The role of the class teacher in student discipline is cooperation with parents, namely the existence of a whatsapp group between parents and homeroom teachers to control, inform and remind each other. giving homework (homework) to distract playing social media. giving attention in the form of advice to be wise with social media. conducting cellphone raids during class hours at school.